Allelopathic potential of alfalfa (Medicago sativa L.) on seed germination and seedling growth of vegetables - Marija Ravlić; Renata Baličević; Marijana Tucak; Matej Mijić; Lucija Stanić; Nikolina Stojanović; Vlatka Skokić (Glasnik Zaštite Bilja, 2021)
The aim of the study was to determine the allelopathic potential of alfalfa (Medicago sativa L.) on seed germination and seedling growth of radish (Raphanus sativus L.), radicchio (Cichorium intybus L. var. foliosum) and tomato (Lycopersicon esculentum Mill.). Water extracts prepared from dry alfalfa biomass in three concentrations (1%, 2.5% and 5%) were tested under laboratory conditions. The allelopathic potential of alfalfa depended on the test species, the water extract concentration, and the measured parameter. The weakest effect was recorded on germination and growth of tomato seedlings. As the concentration of the water extract increased, the negative allelopathic potential also increased. Dry weight of seedlings of test species was the least affected.